Management of aneurysmal subarachnoid hemorrhage - Etminan, Nima; Macdonald, Robert Loch (Critical care neurology, 2017)
Spontaneous subarachnoid hemorrhage (SAH) affects people with a mean age of 55 years. Although there are about 9/100 000 cases per year worldwide, the young age and high morbidity and mortality lead to loss of many years of productive life. Intracranial aneurysms account for 85% of cases. Despite this, the majority of survivors of aneurysmal SAH have cognitive deficits, mood disorders, fatigue, inability to return to work, and executive dysfunction and are often unable to return to their premorbid level of functioning. The main proven interventions to improve outcome are aneurysm repair in a timely fashion by endovascular coiling rather than neurosurgical clipping when feasible and administration of nimodipine. Management also probably is optimized by neurologic intensive care units and multidisciplinary teams. Improved diagnosis, early aneurysm repair, administration of nimodipine, and advanced neurointensive care support may be responsible for improvement in survival from SAH in the last few decades.